Strata Tajuk dan Kompetisi Pertumbuhan Cendana (Santalum album Linn.) di Pulau Timor - Hery Kurniawan (Foresty Faculty of Hasanuddin University, 2012)
Cendana (Santalum album Linn.) is endemic species of NTT Province which not only have economic value, but also as a symbol that unify people or community and culture wisdom in NTT Province. The management of cendana had been passing many time and period, which it has having good and bad experience depending on several factors. Some of these are regional regulation which did not support the efforts for developing cendana plantation. This research was aimed to know cendana crown stratum and competition index especially in private land. Achieving information and data on cendana habitat for supporting the implementation of Cendana Master Plan in NTT Province become the targets of the research. Metodology of the research is descriptive quantitative which based on directly field survey. Data collection was conducted by three ways, which were interviewed with the stakeholders, direct survey and desk studied of secondary data. The result shows that Santalum album trees tend to grow at stratum 1 and 2 of the overall plantation in one area. And the average of competition index of Santalum plantation in TTS regency is 0,18; in TTU regency is 0,07; and Belu regency is 0,1.